Intestinal anti-inflammatory activity of the seeds of Raphanus sativus L. in experimental ulcerative colitis models. (17th February 2016) - Choi, Ki-Choon; Cho, Seong-Wan; Kook, Sung-Ho; Chun, Sa-Ra; Bhattarai, Govinda; Poudel, Sher Bahadur; Kim, Min-Kook; Lee, Kyung-Yeol; Lee, Jeong-Chae
Abstract: Ethnopharmacological relevance: Water extract of Raphanus sativus L. (RSL) seeds was traditionally used to treat digestive inflammatory complaints in Korean culture. RSL seeds exerted antioxidant, anti-inflammatory, and anti-septic functions, suggesting their pharmacological potential for the treatment of inflammatory pathologies associated with oxidative stress such as inflammatory bowel disease. Aim of this study: We evaluated the intestinal anti-inflammatory effects of RSL seed water extract (RWE) in experimental rat models of trinitrobenzenesulphonic acid (TNBS)- or dextran sodium sulfate (DSS)-induced colitis. Materials and methods: RWE was characterized by determining the content of sinapic acid as a reference material and then assayed in the DSS and TNBS models of rat colitis. Male Sprague–Dawley rats were divided into 10 groups ( n =7/group): non-colitic control, DSS or TNBS control, DSS colitis groups treated with RWE (100 mg/kg) or mesalazine (25 mg/kg), and TNBS colitis groups treated with various doses (10, 40, 70, and 100 mg/kg) of RWE or mesalazine (25 mg/kg). RWE or mesalazine treatment started the same day of colitis induction and rats were sacrificed 24 h after the last treatment followed by histological and biochemical analyses. Results: Oral administration with RWE suppressed intestinal inflammatory damages in both DSS- and TNBS-induced colitic rats. The treatment with 100 mg/kg RWE recovered intestinal damages caused by TNBS or DSS to levels similar to that of mesalazine, decreasing the activity of myeloperoxidase activity and the secretion of tumor necrosis factor (TNF)-α and interleukin (IL)-1β. RWE treatment inhibited malondialdehyde production and glutathione reduction in colon of colitis rats. The administration of RWE at dose of 100 mg/kg also suppressed the TNBS- or DSS-stimulated expression of TNF-α, IL-1β, monocyte chemotactic protein-1, inducible nitric oxide, and intercellular adhesion molecule-1 . Furthermore, RWE inhibited p38 kinase and DNA–nuclear factor-κB binding activities, both of which were stimulated in the colitic rats. Conclusions: The current findings show that RWE ameliorates intestinal oxidative and inflammatory damages in DSS and TNBS models of rat colitis, suggesting its beneficial use for the treatment of intestinal inflammatory disorders. Graphical abstract: